Protecting the human rights of persons with disabilities: Islamic perspective and Malaysian legal framework - Fauzi, Husna (Bangladesh Institute of Islamic Thought (BIIT), 2018)
Persons with disabilities are often discriminated against and marginalised from the mainstream development programmes in almost all societies. Being a disadvantaged group, they suffer from social exclusion, denied the basic rights and freedoms enjoyed by everyone else and being deprived of the opportunities to reach their potential. They have a long experience of being perceived as the recipients of welfare and charity rather than rights and respects. In Malaysia, persons with disabilities have been identified as one of the target groups in the National Welfare Policy 1990. The policy aims to uplift the potential and to provide equal opportunities to the disabled persons. Within the span of over thirty years after the endorsement of this policy, the governmental and non-governmental organisations continue to provide various programmes and services to cater for the special needs and interests of the disabled persons. In respect of legal protection provided to the disabled, the enforcement of the Persons with Disabilities Act 2008 seemed by many as particularly timely. This paper discusses the paradigm shift in the model of disability. It provides the statistics of persons with disabilities in Malaysia, highlights the existing policies, programmes and services available to this disadvantaged people and examines the relevant legislation that afford protection to the persons with disabilities in Malaysia.